The Use of Process Mining in Assessing the Risk of Material Misstatement during an Audit: Experimental Evidence - Mugwira, Tatenda; Stuart, Iris; Kulset, Ellen; Nipper, Marvin (Journal of International Accounting Research, 2025)
Using auditors from Germany and Norway as participants, we experimentally investigate two issues of importance when auditors use process mining evidence during an audit: determining the stage of the audit when the evidence is relevant and evaluating whether the presentation format of the evidence makes a difference in the relevance of the evidence. In our experiment, auditors make a risk assessment in the planning or the substantive stage of the audit, while receiving evidence from a process mining tool in either a graph or text format. We find that the process mining evidence is more relevant at the substantive stage of an audit than during the planning stage, and that auditors who receive the process mining evidence in graph format find it slightly more relevant than auditors who receive the evidence in text forma